Dapagliflozin improves left ventricular remodeling and aorta sympathetic tone in a pig model of heart failure with preserved ejection fraction - Nannan Zhang (Cardiovascular Diabetology, 2019)
Abstract Background Heart failure with preserved ejection fraction (HFpEF) is a difficult disease with high morbidity and mortality rates and lacks an effective treatment. Here, we report the therapeutic effect of dapagliflozin, a sodium-glucose cotransporter 2 inhibitor (SGLT2i), on hypertension + hyperlipidemia-induced HFpEF in a pig model. Methods HFpEF pigs were established by infusing a combination of deoxycorticosterone acetate (DOCA) and angiotensin II (Ang II), and Western diet (WD) feeding for 18 weeks. In the 9th week, half of the HFpEF pigs were randomly assigned to receive additional dapagliflozin treatment (10 mg/day) by oral gavage daily for the next 9 weeks. Blood pressure, lipid levels, echocardiography and cardiac hemodynamics for cardiac structural and functional changes, as well as epinephrine and norepinephrine concentrations in the plasma and tissues were measured. After sacrifice, cardiac fibrosis, the distribution of tyrosine hydroxylase (TH), inflammatory factors (IL-6 and TNF-α) and NO-cGMP-PKG pathway activity in the cardiovascular system were also determined. Results Blood pressure, total cholesterol (TC), triglyceride (TG) and low-density lipoprotein (LDL) were markedly increased in HFpEF pigs, but only blood pressure was significantly decreased after 9 weeks of dapagliflozin treatment. By echocardiographic and hemodynamic assessment, dapagliflozin significantly attenuated heart concentric remodeling in HFpEF pigs, but failed to improve diastolic function and compliance with the left ventricle (LV). In the dapagliflozin treatment group, TH expression and norepinephrine concentration in the aorta were strongly mitigated compared to that in the HFpEF group. Moreover, inflammatory cytokines such as IL-6 and TNF-α in aortic tissue were markedly elevated in HFpEF pigs and inhibited by dapagliflozin. Furthermore, the reduced expression of eNOS and the PKG-1 protein and the cGMP content in the aortas of HFpEF pigs were significantly restored after 9 weeks of dapagliflozin treatment. Conclusion 9 weeks of dapagliflozin treatment decreases hypertension and reverses LV concentric remodeling in HFpEF pigs partly by restraining sympathetic tone in the aorta, leading to inhibition of the inflammatory response and NO-cGMP-PKG pathway activation.